Street Tree Density and Distribution: An International Analysis of Five Capital Cities - Smart, Nicholas; Eisenman, Theodore S.; Karvonen, Andrew (Frontiers in Ecology and Evolution, 2020)
Cities around the world are demonstrating significant interest in urban greening to realize a range of socioecological benefits. The urban greening toolkit often includes street trees, an essential component of urban design informed by historic legacies of both human and environmental factors. To date, there has been little comparative analysis of street tree density and distribution across international and intercontinental settings, and associated research has not been situated within the broader discussion on historical legacies. This study focuses on five capital cities (Buenos Aires, Ottawa, Paris, Stockholm and Washington, D.C.) situated in two climate zones and it addresses two research questions: (1) what are the density and distribution of street trees across a given city and its street hierarchy? (2) how do these metrics compare within and between cities by climate zone? The analysis draws upon up-to-date datasets from local authorities and includes geospatial analysis of street trees across hierarchical street classes within the central zones of each city. The results show clear differences in street tree density in cities within and between climate zones as well as differences in street tree distribution in cities within the same climate zone. Substantial differences within climate zones further suggests that cultural factors–including but not limited to urban form, aesthetic norms, and governance regimes–may play a pivotal role in the distribution and density of street trees. This illustrates the importance of place-specific cultural and environmental legacies as determinants of street tree density and distribution and supports further comparative research on the topic.